TINJAUAN TERHADAP KASUS PENCABULAN ANAK DIBAWAH UMUR (PEDOFILIA) SESAMA JENIS DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2014 JO UNDANG-UNDANG NOMOR 17 TAHUN 2016 (STUDI PUTUSAN 90/PID.SUS/2016/PN BMS) - Steven Artaxerxes; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2019)
Children are humans who have physical and mental abilities that are considered weaker to overcome various risks and dangers they face and automatically still depend on other parties, especially family members, but until now mistreatment in sexual matters it still haunts children, especialy pedophiles. One of the cases that occurred was the case of same-sex child molestation carried out by men with the initials BM, against several underage boys, who because of his actions the Judge of the Banyumas District Court stipulated a criminal sentence of 17 (seventeen) years. But in this case, the verdict that was dropped was still far from the word maximum and did not have an impact on the perpetrator. So then, how is the implementation of criminal sanctions against same-sex pedophiles in the verdict 90 / Pid.Sus / 2016 / Pn. Bms according to regulations? The method used in this study is normative legal research. Based on research on several experts and research on related regulations, regarding the decision, it is actually quite good, but it is considered to be less than optimal considering that the pedophile has psychiatric disorders, so psychological rehabilitation is needed and punishment should be made worse so that there is no more other victims for similar cases. It is better, in the future, the judge in determining the decision can consider from all aspects, especially in terms of victims, and psychological aspects of the perpetrators, so that in the future cases of child molestation can be reduced in number.